Effect of eccentric cycling and plyometric training on physiological and performance related parameters of trained junior track cyclists - Sarkar, S.; Dasgupta, S.; Meitei, K. K.; Adhikari, S.; Bandyopadhyay, A.; Dey, S. K. (Polish Journal of Sport and Tourism, 2020)
Introduction: Some certain well-established training protocols exist for developing physical and physiological demands of a track cyclist. But still there is controversy on the effectiveness of combined training protocols. The present study was aimed to investigate the effects of 4-week concurrent eccentric cycling and plyometric training on cycling performance of male cyclists at the pre-competitive phase. Material and methods: A paired study design was applied to 15 young (15.04 ± 1.01 yrs) Indian male track cyclists to assess the effects of proposed concurrent training protocol on body composition and various physical fitness parameters. Results: Hydration status [TBW (~1%) and ICW (~1%)], glycogen content (~3%), muscular strength (~6-11%), trunk flexibility (~5%), anaerobic power output (~9%), endurance capacity (~5%), acceleration (~7%), leg explosive strength (~7%) and agility (~2%) were found to be improved significantly after the 4-week concurrent training protocol. Conclusions: The concurrent intervening physical training protocol was intended to increase muscular hypertrophy, peripheral factor gradient, glycolytic and oxidative enzyme capacity with proper neuromuscular coordination which may ultimately help the cyclists to pedal at a faster rate with higher muscular power output even for longer time.